Diseño y construcción de un sistema basado en IoT para la monitorización y el control del consumo energético residencial a través de power line communications (PLC) - Riofrio Irene, Jonathan Andrés (2025)
In this work, the design and construction of a monitoring and control system for residential energy consumption was carried out using the Internet of Things paradigm and power line communications technology. This combination enables efficient energy management by leveraging the existing electrical line infrastructure to transmit data, eliminating the need for new wiring. The implementation of this system allows not only real-time monitoring of energy consumption but also remote control of circuit switching on and off. The main results obtained include: the design of the network topology within the IoT framework, the representation of system components using a one-line diagram, the construction of a power grid anchoring panel, the development of firmware (programming code), the generation of real-time graphs and datasets of the circuits’ electricity consumption, real-time data interpretation of a typical day, and a rapid response when executing an on/off instruction from the online platform to the master device. This creates an opportunity to apply this solution in broader environments, with the potential to improve energy efficiency and reduce operating costs. The system's security in a domestic setting focuses on the configuration of a private PLC network with AES-128 encryption (specific to powerline adapters). Additionally, the user interface is intuitive, making it easy for users without advanced technical knowledge to access and control the system. This work contributes to residential energy management, promoting sustainability by reducing energy consumption and reliance on non-renewable sources. Keywords: monitoring, energy, PLC, IoT.